Angola : Third Review under the Extended Arrangement Under the Extended Fund Facility, Requests for Augmentation and Rephasing of Access, Waivers of Nonobservance of Performance Criterion and Applicability of Performance Criterion, Modifications of Performance Criteria, and Completion of Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2020)
The economic outlook has substantially deteriorated since the Second Review, driven by the negative effects of the COVID-19 pandemic on global economic activity and oil prices. The adverse impact of the shock on the Angolan economy, which is highly dependent on oil (95 percent of exports, two-thirds of government revenue), adds to the hardship from five consecutive years of recession. Rapid exchange rate depreciation and the decline in oil prices have pushed the public debt-to-GDP ratio to a very high level. However, continued fiscal retrenchment, prudent debt management, and debt reprofiling are expected to improve debt dynamics progressively.